Penanaman Nilai Moral dan Pengetahuan Hukum untuk Mengantisipasi Kenakalan Remaja di SMK 8 Medan - Sri Banun; Muhammad Azmi (Nusantara Mengabdi Kepada Negeri, 2025)
Adolescence is the stage where a child's puberty occurs before reaching adulthood, this is a process that every child must go through between the ages of 12 and 18. At this stage, children who are growing up generally experience several changes both physically, emotionally, and emotionally, becoming more sensitive to circumstances and desires or high curiosity about their environment. In conditions like this, the role of several parties and knowledge is very necessary to control and supervise without having to restrain so as to hinder the development of the teenager, these parties include parents, family, teachers, and the community. Based on this, it is felt necessary to carry out socialization and a direct approach to convey the importance of knowledge or science to fortify adolescent behavior so that a situation that exceeds the limit does not occur such as promiscuity, free sex and other negative influences that must be directly conveyed to the teenager. From this service, a report was made as a form of steps that have been taken as an effort to protect the generation with knowledge in the digital era for the future. In addition, in facing the increasingly rapidly developing digital era, teenagers are very vulnerable to the influence of social media and the flow of information that is so fast and unlimited. Easy access to various digital platforms can have positive impacts if used wisely, but it also has the potential to lead teens to negative content if not properly supported. Therefore, digital literacy is a crucial skill for teens to master, enabling them to select information, convey critical messages, and use technology responsibly.